GLOBALISASI DAN DAKWAH DI ERA MILENIAL - Jamal, Ghofir; Salma Nur, Amalina (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2022)
Abstract: Globalization, whether we realize it or not, has had a great impact and influence on society, not only in the economic, trade, political, labor fields, but also in the social, cultural and religious fields. In fact, globalization has brought and created new problems in society. Among them are the so-called “fundamental change”, namely rapid and fundamental changes as a result of advances (revolution) in communication and information technology. We need to realize that globalization is not only a threat, but also an opportunity for da'wah to spread Islam and strengthen its teachings on earth. Globalization opens up new opportunities and opportunities for Muslims to preach. Global da'wah is the obligation of Muslims as a logical consequence of the position of Islam with the religion of mercy for the whole world. The renewal of da'wah needs to be carried out because Muslims must move forward and are oriented towards progress or better conditions in all things, including da'wah affairs. Changes that arise due to the development and progress of the times that occur in this new century naturally demand changes and renewal of da'wah. Da'wah in ancient times was different from da'wah in today's digital age.